2019
DOI: 10.1055/s-0039-1685160
|View full text |Cite
|
Sign up to set email alerts
|

Aperture and Suspensory Fixation Equally Efficacious for Quadriceps Tendon Graft Fixation in Primary ACL Reconstruction: A Systematic Review

Abstract: This review is aimed to compare suspensory and aperture quadriceps tendon autograft femoral and tibial fixations in primary anterior cruciate ligament reconstruction (ACL-R), and the clinical outcomes and complication profiles of each fixation method. Greater understanding of the optimal graft fixation technique for quadriceps tendon (QT) autografts may assist surgeons in improving outcomes after ACL-R. PubMed, Embase, and Medline were searched from database inception to September 2017, and again to July 2018,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 78 publications
(75 reference statements)
0
12
0
Order By: Relevance
“…Another systematic review looking at graft fixation found no difference in graft re-rupture rate or clinical outcomes between aperture versus suspensory fixation of QT. 40 None of the aforementioned reviews compared all soft-tissue QT to QT grafts including a bone plug, and further studies will be valuable in this area. Theoretical benefits to all-soft tissue QT include mitigated risk of patellar fracture and reduced donor site morbidity, although these are rarely reported, and can be minimized by harvesting less than 30% of the patella 41 .…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Another systematic review looking at graft fixation found no difference in graft re-rupture rate or clinical outcomes between aperture versus suspensory fixation of QT. 40 None of the aforementioned reviews compared all soft-tissue QT to QT grafts including a bone plug, and further studies will be valuable in this area. Theoretical benefits to all-soft tissue QT include mitigated risk of patellar fracture and reduced donor site morbidity, although these are rarely reported, and can be minimized by harvesting less than 30% of the patella 41 .…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Nevertheless, adjustable suspensory femoral fixation has been long used in ACL reconstruction, with great biomechanical and clinical results using the QT graft, 16 hamstring graft, 17 , 18 and bone-patella-tendon-bone graft. 19 …”
Section: Discussionmentioning
confidence: 99%
“…For preparation of the hamstring tendon graft, the gracilis and semitendinosus strands were looped through a closed-loop extracortical button suspensory device 3,11,45,53 and then doubled and whip-stitched together using braided polyester No. 2 suture (Arthrex).…”
Section: Methodsmentioning
confidence: 99%
“…Soft tissue autografts 57 were harvested from the tested knee, with the quadriceps tendon used for ACL 3,11 reconstruction (sized to 9.0 mm), while for the PCL, a hamstring tendon autograft (semitendinosus and gracilis, quadrupled loop) was used in the majority of cases, and an additional allograft strand was added, if needed, to reconstruct the PCL 36,51 (sized to 9.5 mm) (Figure 1).…”
Section: Surgical Proceduresmentioning
confidence: 99%